Esquema de planeación estratégica sostenible para la empresa Codech Ingenieria S.A.S en el sector de la construcción para el periodo 2023 al 2028 (2023)
In a constantly evolving world, companies in the construction sector are facing unprecedented challenges and exciting opportunities. CODECH INGENIERÍA, a company with a long history in the construction sector, is no stranger to these changes. In this degree work, we will explore detailed and insightful strategic planning designed to strengthen and guide CODECH INGENIERÍA S.A.S in its pursuit of a sustainable and successful future. The construction industry is a vital engine for economic growth and development. However, competition is fierce, customer expectations are increasingly demanding, and sustainability has become a fundamental pillar. CODECH INGENIERÍA S.A.S is at a crucial point in its history, where strategic decisions will take a central role in defining its continued success.